Fatty Acids Composition of Red and Purple Pomegranate (Punica granatum L) Seed Oil - Soetjipto, Hartati; Pradipta, Murda; Timotius, KH (Indonesian Research Gateway, 2010)
The aim of this investigation was to determine the content and composition ofÃÂ fatty acid in seed oil of red and purple pomegranate (ÃÂ Punica granatum L). The extraction process was performed by Soxhlet extractor with petroleum ether as solvent. The separation and identification of pomegranate seed oil was done by using GCMS. The total oil content of red and purpleÃÂ pomegranateÃÂ were 128 g/kg d.wÃÂ and 103 g/kg d.w respectively. Both showed the same major fatty acidsÃÂ as palmitic, stearic, oleic, linoleic andÃÂ punisic acid. Oleic acid ( 19-21% ) and linoleic acid ( 20-21% ) were found as the mostÃÂ dominant fatty acids in red pomegranate, whereas purple pomegranate seed oil was dominated by oleic acid ( 41-43% ) and punicic acidÃÂ ( 0-25% ). Neutral lipidÃÂ fraction ofÃÂ red and purple pomegranate seed oils was more dominantthan glycolipid and phospholipid. NeutralÃÂ lipid fractionÃÂ of red and purple pomegranate seed oil wereÃÂ 89 % and 91% respectively.ÃÂ Glycolipid fractionÃÂ of red and purple pomegranate seed oil were 8 % and 5 % , whereas phosholipid fraction of red and purple pomegranate seed oil were 3 % and 4 %. The punicic acid content ofÃÂ total lipid ofÃÂ purple pomegranate seed oil ( PPSO ) (0-25% ) was higher than red pomegranate ( RPSO ) ( 9-16% ). On the contrary neutral lipid of red pomegranate showed higher punicic acid content (54-75%) than the purple pomegranate (14-55% ). Glycolipid of red pomegranate containedÃÂ punicic acidÃÂ ( 0-42%). The punicic acidcontentÃÂ of the phospholipid fraction ofÃÂ red pomegranate was higher ( 0-22 % ) than the one ofÃÂ purple pomegranate (0-2% ).